Design and application of SPWM based 21-level hybrid inverter for induction motor drive - Meraj, S.T. (Turkiye Klinikleri, 2020)
This paper presents the application of a newly developed 21-level hybrid multilevel inverter. A high frequency modulation technique known as sinusoidal pulse width modulation (SPWM) is applied to the hybrid inverter. This modulation methodology operates the switching sequences of the multilevel inverter to produce the desired 21-level output voltage. To validate the proper application of this inverter, it is further utilized to maintain the speed of a single phase induction motor. The velocity control of the motor is established on the principle of V/f control technique. The speed control strategy along with the compatibility of the SPWM modulation technique were verified by means of simulation and experimental results. Â© TÃBÄ°TAK